2018
DOI: 10.1177/0306624x18785100
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Storytelling: The Experiences of Incarcerated Women Sharing Their Stories

Abstract: Women are the fastest growing prison population in the United States. Women who are incarcerated are characterized by significant mental health needs and intense societal stigma. Despite such vulnerabilities, little is known about their experiences or the pathways that lead them toward recovery and rehabilitation. This qualitative research explores the lived experiences of incarcerated women sharing their stories with high school students and their teachers as part of a community outreach project entitled "Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
5
23
0
1
Order By: Relevance
“…Additionally, storytelling as the primary modality was found in communicable disease research in public health and medical anthropology (Frank et al, 2015;Gilliam et al, 2012;Kleinman & Benson, 2006;Le et al, 2017;Mohammadhosseini et al, 2016;Willis et al, 2014). Finally, the literature showed that primarily public health researchers and medical anthropologists implemented storytelling in their studies, with a few identified in criminology and agriculture (Bove & Tryon, 2018).…”
Section: How Was Storytelling Specifically Used?mentioning
confidence: 99%
“…Additionally, storytelling as the primary modality was found in communicable disease research in public health and medical anthropology (Frank et al, 2015;Gilliam et al, 2012;Kleinman & Benson, 2006;Le et al, 2017;Mohammadhosseini et al, 2016;Willis et al, 2014). Finally, the literature showed that primarily public health researchers and medical anthropologists implemented storytelling in their studies, with a few identified in criminology and agriculture (Bove & Tryon, 2018).…”
Section: How Was Storytelling Specifically Used?mentioning
confidence: 99%
“…A study with male participants described high levels of stress and negative impact of imprisonment on preexisting mental illness as main mental health challenges (Oliffe et al, 2018) whereas other qualitative findings suggest long periods of isolation and negative relationships between staff and prisoners to be associated with poor mental health (Nurse et al, 2003). The participation in qualitative interviews itself can be experienced as beneficial by imprisoned study participants, which might be due to similar positive effects as from storytelling within a context of incarceration (Rivlin et al, 2011;Bove and Tryon, 2018). The results of prison research may be applied in programs to relieve the burden of mental health symptoms and to reduce criminal recidivism.…”
Section: Introductionmentioning
confidence: 99%
“…Disqualification of incarcerated women’s voices is often achieved through denying them opportunities to share their experiences and distorting their opinions. Authors (Bove & Tryon, 2018; Dastile, 2013; Sandoval & Baumgartner, 2017) make a case for uncovering counterstories to the dominant narratives and discourses about incarcerated women. Such uncovering of women offenders’ stories needs to be done through allowing them an opportunity to craft their stories, as they are experts in their own right in constructing their own life histories (Dastile, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This account of women classified as maximum-security offenders is often characterised by incomplete stories with distortions and negative labelling. Very few studies (Bove & Tryon, 2018; Fili, 2013; Kruttschnitt & Carbone-Lopez, 2006; Schram et al, 2004; Silverman, 2001) have examined how women construct their incarceration identities. Dissel (1996) also indicated that maximum-security offenders are often not included in rehabilitation processes and tend to be treated in a routine and inflexible manner due to concerns about security risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation